The use of Taguchi method to determine factors affecting the performance of destination sequence distance vector routing protocol in mobile ad hoc networks - Mohamed H.; Lee M.H.; Sarahintu M.; Salleh S.; Sanugi B. (2024)
Indexed by Scopus